Quality Analysis of Microbiological and Organoleptic of Anchovy (Stolephorus sp.) with Boiling Treatment in Toniku, West Halmahera - Djamhur, Martini; Achmad, M. Djanib; Hidayat, Rian (Sangia Research Media and Publishing, 2020)
The quality of anchovy is very dependent on handling and processing, the stages of good anchovy handling are caught fish, washed with clean fresh water, drained fish, dried fish in the sun at 37-40oC, packaged fish and marketed fish. Good handling and processing will produce high quality anchovy. The research objectives were: To determine the quality of anchovy by microorganism and organoleptic tests. The research benefit is to obtain the quality of anchovy which is expected to have an economic effect on fishermen. This study used an exploratory method with direct sampling techniques on the results of catching anchovies on the boat chart fishing gear in Toniku, West Halmahera. The results showed the total density. The test results of microorganisms from 3 (three) samples, the highest TPC value in community anchovy samples (TM), the identification results obtained by three types of bacteria, namely Micrococus, Bacillus, and Stapylococus and organoleptic test results from 3 (three) samples. shows that the average value of the highest level of preference in samples of boiled anchovies with salt (TRG).